2021
DOI: 10.1097/sih.0000000000000575
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Communication and Safety Behaviors During Hospital-Wide Code Response Simulation

Abstract: Introduction: To understand the baseline quality of team communication behaviors at our organization, we implemented institution-wide simulation training and measured the performance of safety behaviors of ad hoc teams in emergent situations. Methods: Clinicians participated in 2 interprofessional video-recorded simulation scenarios, each followed by debriefing. Using a standardized evaluation instrument, 2 reviewers independently evaluated the presence or absence of desired team safety behaviors, including es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…This perception is supported by Smith et al [ 38 ], who proved that staffing level influenced the rate of failure to adequately respond to deranged vital signs. Altogether, the findings confirmed the previously identified issues and need for improvements in the care of patients in general hospital wards [ 1 , 3 , 5 , 21 , 39 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This perception is supported by Smith et al [ 38 ], who proved that staffing level influenced the rate of failure to adequately respond to deranged vital signs. Altogether, the findings confirmed the previously identified issues and need for improvements in the care of patients in general hospital wards [ 1 , 3 , 5 , 21 , 39 ].…”
Section: Discussionsupporting
confidence: 86%
“…Applying CRM creates a climate that encourages an open attitude with the opportunity for everyone on the team, regardless of profession or title, to speak-up for patient safety if something feels wrong [ 20 ]. However, in practice, there is a variable performance on completing the safety behaviors prescribed in CRM [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found that adverse events decreased when team members used CLC, 14,16,17 whereas others reported that tasks were completed significantly faster with CLC, compared with nonstructured communication 12,16 . Most studies examining CLC were based on simulated emergencies 15,17–26 ; however, few have investigated the use of CLC in clinical practice 12,14,27 . The aim of this study was therefore to explore the use of CLC among anesthesia personnel in real-life interprofessional emergency teams.…”
Section: Introductionmentioning
confidence: 99%